Bidirectional associations between mental health conditions and cognitive impairment in patients with pain conditions of the back, neck, and spine: A population-based study - Mohammad Alipour-Vaezi; Jyoti Savla; Margaret R. Rukstalis; Daniel B. Rukstalis; Kwok-Leung Tsui; Donald B. Penzien; Robert S. McNamara; Huaiyang Zhong (PLoS ONE, 2026)
Background Pain conditions (PCs) of the back, neck, and spine are frequently accompanied by psychiatric and cognitive comorbidities in older adults. However, the directionality and magnitude of the associations between psychiatric disorders and cognitive impairment in this population remain insufficiently characterized. Objective This population-based study examines the bidirectional relationship between Mental Health Conditions (MHCs) and Cognitive Impairment (CI) among patients with back, neck, and spine pain. It assesses whether MHCs—including depression, Bipolar Disorder (BD), Generalized Anxiety Disorder (GAD), Post-Traumatic Stress Disorder (PTSD), Panic Disorder (PaD), Persistent Mood Disorder (PMD), Suicidal Behavior (SB), Schizophrenia (SCZ), and Substance Use Disorder (SUD)—are associated with subsequent incident CI, and conversely, whether prior CI is associated with subsequent incident MHCs. Methods Data were drawn from the TriNetX US Collaborative Network (2016/01/01–2021/12/31), comprising over 119 million patients. Cohorts of patients with PCs were defined using ICD-10 codes. Propensity score matching was applied to balance demographics and comorbidities. Kaplan-Meier survival analysis assessed risks over a three-year follow-up. Results A bidirectional association was observed between MHCs and CI. PC Patients with MHCs had a higher three-year risk for CI, with the largest risk ratios (RR) observed for SCZ (RR: 4.594; 95% Confidence Interval [3.974, 5.312]) and BD (RR: 3.761[3.247, 4.356]). Other MHCs, including depression, PMD, GAD, PTSD, PaD, and SUD, were also associated with higher CI risk. Conversely, patients with pre-existing CI exhibited a higher three-year risk for subsequent MHCs, particularly BD (RR: 4.818 [3.045, 7.624]), SCZ (RR: 3.398 [2.874, 4.017]) and SB (RR: 1.913 [1.340, 2.732]). Conclusion Our findings indicate a bidirectional relationship between MHCs and CI among older adults with documented back, neck, and spine pain. Integrated screening and coordinated multidisciplinary care may help identify psychiatric and cognitive comorbidities earlier and support more comprehensive management of this medically complex population.